2016
DOI: 10.1007/s11064-016-1854-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of S-Phase Arrest in Human Glioma Cells by Selenocysteine, a Natural Selenium-Containing Agent Via Triggering Reactive Oxygen Species-Mediated DNA Damage and Modulating MAPKs and AKT Pathways

Abstract: Selenocysteine (SeC) a natural available selenoamino acid exhibits novel anticancer activities against human cancer cell lines. However, the growth inhibitory effect and mechanism of SeC in human glioma cells remain unclear. The present study reveals that SeC time- and dose-dependently inhibited U251 and U87 human glioma cells growth by induction of S-phase cell cycle arrest, followed by the marked decrease of cyclin A. SeC-induced S-phase arrest was achieved by inducing DNA damage through triggering generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Previous studies have found that SeC inhibited human glioma cells growth in 48 h mainly by induction of S-phase arrest through triggering ROS-mediated DNA damage 5 . To explore the oxidative status in SeC-induced apoptosis, we subsequently investigated the ROS generation and several oxidative damage markers.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies have found that SeC inhibited human glioma cells growth in 48 h mainly by induction of S-phase arrest through triggering ROS-mediated DNA damage 5 . To explore the oxidative status in SeC-induced apoptosis, we subsequently investigated the ROS generation and several oxidative damage markers.…”
Section: Resultsmentioning
confidence: 91%
“…The kinetics course of ROS generation in U251 cells was monitored using a DCFH-DA probe in 2 h. The mitochondrial superoxide anion in living U251 cells was vividly imaged by Mito-SOX, a mitochondria-targeted red probe. The experimental details of the three detective methods were carried out according to our previous report 5 . All experiments were conducted in accordance with the relevant guidelines and regulations of Taishan Medical University.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations